Перспективы развития тонкопленочных микросборок - Spirin, V. G. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
Based on the analysis of certain structural and technological options, the prospects for increasing the integration of thin-film microassemblies with substrates made of sitall, polycor, sapphire, and silicon are considered. The technology for manufacturing chromium resistors on silicon is described. An assessment of the packing density of printed and silicon boards is provided.